2018
DOI: 10.1186/s13104-018-3889-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of vegetables sold in Arba Minch Town, Southern Ethiopia

Abstract: ObjectiveUnhygienically handled fruits and vegetables which are usually consumed in raw serve to transmit various infectious diseases. Bacteria are among the common vegetable contaminants. However, the species of contaminants and rate of contamination depends on various environmental and human factors. Hence, a cross-sectional study was conducted to assess the level of bacterial contamination and associated factors among vegetables marketed in Arba Minch town from January to March, 2018. A structured questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
3
25
2
Order By: Relevance
“…Likewise, tomatoes, onions carrots, ripe banana and Chinese cabbage had considerable high pathogenic contaminations while the least contaminated were okra and avocadoes. These findings are similar to the previous studies, but only cabbage was highly contaminated [7]. High contamination of these leafy vegetables emanates from the large surface area, contaminated water splashed to freshen, and possible unhygienic handling by farmers and vegetable vendors as well as customers touching during selection of vegetables.…”
Section: Bacterial Contaminationsupporting
confidence: 90%
See 3 more Smart Citations
“…Likewise, tomatoes, onions carrots, ripe banana and Chinese cabbage had considerable high pathogenic contaminations while the least contaminated were okra and avocadoes. These findings are similar to the previous studies, but only cabbage was highly contaminated [7]. High contamination of these leafy vegetables emanates from the large surface area, contaminated water splashed to freshen, and possible unhygienic handling by farmers and vegetable vendors as well as customers touching during selection of vegetables.…”
Section: Bacterial Contaminationsupporting
confidence: 90%
“…A considerable high proportion (63.2%) of samples tested was contaminated with at least one bacterial pathogen. This prevalence in higher than the rate reported in Ethiopia where only 48.7% were positive for bacterial contamination [7]. Pathogenic bacteria including E. coli and Salmonella spp were isolated from fresh vegetables, contrary to the study in Brazil which did not report Salmonella spp.…”
Section: Bacterial Contaminationcontrasting
confidence: 85%
See 2 more Smart Citations
“…Consumption of any of these organisms poses a serious health hazard. Previous reports where E. coli and Salmonella spp were isolated from cabbage include the following: Eni et al, (2010) reported E. coli (4.2%), Salmonella spp (12.5%) from Sango Ota, Nigeria; Mritunjay and Kumar, (2017) and Alemu et al, (2018) reported E. coli (16.7%) and (31.4%) respectively from Dhambad city, India and Arba Minch town, Southern Ethiopia.…”
Section: Bacteria Isolatedmentioning
confidence: 99%